Carving wood and stone : an illustrated manual - Prince, Arnold (New Jersey : Prentice-Hall, 1981)
Direct carving can be described as the art of creating a piece of sculpture from a block of material by the process of removing or subtracting parts of the block in such a way that the unremoved portions of the block express the sculptor's intent.
1. Carving stone -- 2. Stonecarving tools -- 3. How to carve a piece of stone -- 4. Carving marble and alabaster -- 5. Polishing and finishing stone -- 6. Carving wood -- 7. Woodcarving tools -- 8. Carving a log -- 9. Laminates wood -- 10. Finishing wood sculpture -- 11. Carving and adding -- 12. Relief sculpture.
Includes index.
Keywords: WOOD AND STONE -- CARVING